154k views
3 votes
6x−3(6−5x)+3x=10−4(2−x)

1 Answer

6 votes

Answer:

x =1

Explanation:


6x-3\left(6-5x\right)+3x=10-4\left(2-x\right)\\\\Group\:like\terms\\6x+3x-3\left(-5x+6\right)=10-4\left(2-x\right)\\\\Add\:similar\:elements:\:6x+3x=9x\\9x-3\left(-5x+6\right)=10-4\left(2-x\right)\\\\Expand\:-3\left(-5x+6\right):\quad 15x-18\\9x+15x-18=10-4\left(2-x\right)\\\\\mathrm{Add\:similar\:elements:}\:9x+15x=24x\\24x-18=10-4\left(2-x\right)\\\\Expand\:10-4(2-x):4x+2\\24x-18=4x+2\\\\Add\:18\:to\:both\:sides\\24x-18+18=4x+2+18\\\\Simplify\\24x=4x+20\\


\mathrm{Subtract\:}4x\mathrm{\:from\:both\:sides}\\24x-4x=4x+20-4x\\\\Simplify\\20x=20\\\\\mathrm{Divide\:both\:sides\:by\:}20\\(20x)/(20)=(20)/(20)\\\\Simplify\\x=1

User Dennis Kriechel
by
6.0k points